Binary patterning of polar and nonpolar amino acids in the sequences and structures of native proteins. - West, M. W. (Cold Spring Harbor Laboratory Press, 1995)
Protein sequences can be represented as binary patterns of polar ([symbol: see text]) and nonpolar ([symbol: see text]) amino acids. These binary sequence patterns are categorized into two classes: Class A patterns match the structural repeat of an idealized amphiphilic alpha-helix (3.6 residues per turn), and class B patterns match the structural repeat of an idealized amphiphilic beta-strand (2 residues per turn). The difference between these two classes of sequence patterns has led to a strategy for de novo protein design based on binary patterning of polar and nonpolar amino acids. Here we ask whether similar binary patterning is incorporated in the sequences and structures of natural proteins. Analysis of the Protein Data Bank demonstrates the following. (1) Class A sequence patterns occur considerably more frequently in the sequences of natural proteins that would be expected at random, but class B patterns occur less often than expected. (2) Each pattern is found predominantly in the secondary structure expected from the binary strategy for protein design. Thus, class A patterns are found more frequently in alpha-helices than in beta-strands, and class B patterns are found more frequently in beta-strands than in alpha-helices. (3) Among the alpha-helices of natural proteins, the most commonly used binary patterns are indeed the class A patterns. (4) Among all beta-strands in the database, the most commonly used binary patterns are not the expected class B patterns. (5) However, for solvent-exposed beta-strands, the correlation is striking: All beta-strands in the database that contain the class B patterns are exposed to solvent.(ABSTRACT TRUNCATED AT 250 WORDS)